Progress Report on the Activities of the Independent Evaluation Office. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
Since its April 2007 Report to the IMFC, the IEO has released its report on The IMF's Advice on Exchange Rate Policy, continued work on three other evaluations, and issued its Annual Report for 2006-07.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Evaluation; Exchange Rate; IEO; Policy Initiative; PP